Writing and Being Human - Centeno, Jeffrey M. (2021)
Truth is as moral as political in nature. This relation must be asserted more than ever, especially when seen against the background of today's social media phenomenon, where people express their views about anything and anyone at an unprecedented speed and reach. Within the context of the academic world, the search for truth serves as the moral foundation of authorship and guides the practice of academic freedom. Teaching by writing affects the formation of fellow human beings for good or ill. Thus, every author must write only what is true, in view of communicating factual information, and not "fake news." Before a deluge of information on social media, academics must always ask the critical question: Is this true?
Keywords: Authorship; Academic freedom; Research; Academic writing; Writing processes; Writing; Social media